2021
DOI: 10.3390/ijerph18179164
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Coagulant versus Industrially Used Coagulants: Identification of Their Coagulation Performance, Mechanism and Optimization in Water Treatment Process

Abstract: The evaluation of complex organic and inorganic coagulant’s performances and their relationships could compromise the surface water treatment process time and its efficiency. In this work, process optimization was investigated by comparing an eco-friendly chitosan with the industrially used coagulants namely aluminum sulfate (alum), polyaluminum chloride (PAC), and aluminum chlorohydrate (ACH) in compliance with national drinking water standards. To treat various water samples from different treatment plants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…It is also reported to provide NOM removal efficiencies comparable to those of metal-based coagulants. For instance, Khairul Zaman et al [49] carried out a study on the comparison of performances between different types of industrially used aluminum-based coagulants (aluminum sulfate, polyaluminum chloride, and aluminum chlorohydrate) and biocoagulant chitosan for the treatment of surface waters with different turbidities. It was concluded that chitosan is capable of performing comparably to aluminum chlorohydrate, although under different conditions, namely in an acidic environment [49].…”
Section: Biocoagulantsmentioning
confidence: 99%
“…It is also reported to provide NOM removal efficiencies comparable to those of metal-based coagulants. For instance, Khairul Zaman et al [49] carried out a study on the comparison of performances between different types of industrially used aluminum-based coagulants (aluminum sulfate, polyaluminum chloride, and aluminum chlorohydrate) and biocoagulant chitosan for the treatment of surface waters with different turbidities. It was concluded that chitosan is capable of performing comparably to aluminum chlorohydrate, although under different conditions, namely in an acidic environment [49].…”
Section: Biocoagulantsmentioning
confidence: 99%
“…In the research initiated as a result of increasing studies on the effects of Al intake through potable water in the Langat River Basin in Malaysia; To determine Al 3+ concentrations by Inductively Coupled Plasma Mass Spectrometry (ICP-MS), water samples from the basin water were examined between 2015 and 2016. It has been stated that the doses of Al2(SO4)3 used in water disinfection are very important to protect health (Ahmed et al, 2019;Khairul Zaman et al, 2021).…”
Section: Aluminum and Fluorine In Drinking Water Andmentioning
confidence: 99%
“…Coagulants, which are hydrolyzing metal salts (Fe or Al), are often used in the coagulation process to destabilize colloids. To date, coagulants have been the subject of much study and development with the goal of creating a safer environment, having high stability, and more adaptable formulations that can withstand a wide range of processing conditions without compromising coagulation efficiency [20]. During water treatment processes, conventional coagulants such as iron and aluminium sulfate are typically used to stimulate particle formation.…”
Section: Introductionmentioning
confidence: 99%